1995
DOI: 10.1016/0169-4332(94)00405-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser wavelength and fluence on the growth of ZnO thin films by pulsed laser deposition

Abstract: Transparent, electrically conductive and c-axis oriented ZnO thin films have been grown by the pulsed laser deposition (PLD) technique on silicon and Coming glass substrates employing either a KrF excimer laser (3. = 248 nm) or a frequency-doubled Nd:YAG laser (3. = 532 rim). The crystalline structure, surface morphology, optical and electrical properties of the deposited films were found to depend not only on the substrate temperature and oxygen partial pressure, but also on the irradiation conditions. The qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…It has already been shown that the pulsed laser deposition (PLD) method can be used to grow highquality c-axis oriented ZnO films on Si or glass substrates at lower temperatures than most other techniques [13, 141. In this letter we show that by employing the optimised deposition conditions previously determined [14], ZnO films having a crystalline structure amongst the best reported so far by any technique can also be grown on GaAs substrates using the PLD method.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown that the pulsed laser deposition (PLD) method can be used to grow highquality c-axis oriented ZnO films on Si or glass substrates at lower temperatures than most other techniques [13, 141. In this letter we show that by employing the optimised deposition conditions previously determined [14], ZnO films having a crystalline structure amongst the best reported so far by any technique can also be grown on GaAs substrates using the PLD method.…”
Section: Introductionmentioning
confidence: 99%
“…The inset in Fig. 2 shows a selected area electron diffraction where the electron beam is parallel to the [21][22][23][24][25][26][27][28][29][30] zone axis of the ZnO. The indexed diffraction pattern confirms the hexagonal structure of the ZnO thin film.…”
Section: Resultsmentioning
confidence: 79%
“…The deposition temperature is 500°C, and the thickness of Zn film is 800 nm. The use of 248 nm KrF excimer radiation for ZnO ablation was found in previous research to produce films of significantly higher quality than those grown using longer wavelength radiation [21][22][23]. Furthermore, ablation with 248-nm radiation leads to a smooth target surface after ablation [24] and, hence, all targets used here were pre-ablated prior to initial deposition, and not polished between depositions.…”
Section: Methodsmentioning
confidence: 99%
“…No obstante, la figura 2 muestra la formaci-n de un ZnO orientado [001]ZnO||[100]InP obtenido cuando el substrato se calienta a 350-400 o C en 0.1 mbar de presi-n de ox'geno, teniendo un h ‡bito de crecimiento columnar sin orden aparente en el plano del substrato. Se observa una alta calidad cristalina para la familia de planos {00l} (FWHM=0.20 O y ω-FWHM=2.6 O para un espesor de 260 nm) comparable con la reportada para el ZnO, sobre Si (31). La rugosidad medida corresponde al 3% del espesor de la l ‡mina depositada.…”
Section: Tiempo De Erosión (Min)unclassified